Siapa Konsumen Kita? : Analisis Perubahan Konsumen Di Era ”Ekonomi Baru” - C. T. Adhikara (The Winners, 2005)
Economy has shifted into a new space. It’s often called New Economy or Digital Economy or Internet Economy. The characteristic of New Economy is signed by technology application using internet in every sector, limitless of trade time and space.Speed is an important element for everything. It also affects consumer. Who is company’s real consumer in this New Economy?